CaDMR1 Cosegregates with QTL Pc5.1 for Resistance to Phytophthora capsici in Pepper (Capsicum annuum). Issue 2 (1st July 2014) - Rehrig, William Z.; Ashrafi, Hamid; Hill, Theresa; Prince, James; Van Deynze, Allen
Abstract : A major problem for the pepper ( Capsicum annuum ) industry is the root rot disease caused by Phytophthora capsici ( Pc ), to which all commercial varieties suffer yield losses despite good management practices and available landraces with high levels of resistance. A high‐density map with 3887 markers was generated in a set of recombinant inbred lines (RIL) derived from the highly resistant Capsicum annuum accession Criollo de Morelos‐334 and Early Jalapeño. These lines have been systematically screened for Pc resistance against a set of isolates collected from Mexico, New Mexico, New Jersey, California, Michigan and Tennessee. Quantitative trait loci (QTL) associated with effective resistance across isolates have been identified and validated with SNP markers across additional segregating populations. By leveraging transcriptomic and genomic information, we describe CaDMR1, a homoserine kinase (HSK), as a candidate gene responsible for the major QTL on chromosome P5 for resistance to Pc . SNP markers for the resistant allele were validated to facilitate gene pyramiding schemes for recurrent selection in pepper.